Risk Assessment in Mining-Related Project Management - Vaněk, Michal; Tomášková, Yveta; Straková, Alena; Špakovská, Kateřina; Bora, Petr (GeoScience Engineering, 2013)
Risk assessment is an integral part of the assessment of an investment project. Underestimating risks may lead to erroneous conclusions with negative impacts on the economy of the project. With regard to the level of investments and the time factor under mining company conditions, the issue of risk gains importance. The evaluation of existing practical experience shows that managers of mining companies more often approach to the risk assessment based on intuition, than through exact methods. The article is devoted to the risk assessment itself whose procedure is illustrated on a model example of assessing continuous and discontinuous alternatives of exploitation of loose overburden materials during large-scale coal mining operations in progress at pit quarries.